Isolation of BHV-1 from an outbreak of abortion in an organized herd - MEHROTRA, M L; SINGH, K P; KHANNA, P N; SHUKLA, D C (The Indian Journal of Animal Sciences, 2013)
Bovine herpes virus 1 was isolated from a cow during storm of abortion in an organized herd. The virus was identified by its physico-chemical and serological characters. The role of stress factors in the causation of disease are discussed